Perlindungan Hukum terhadap Kreditur Akibat Wanprestasi dalam Perjanjian Hutang Piutang yang Diikuti dengan Akta PPJB dan Kuasa Menjual: Studi Putusan Pengadilan Negeri Kepanjen Nomor 124/PDT.G/2019/PN.KPN - Evlin Yosephin Natazza Simanjuntak; Hasim Purba; Mahmul Siregar (Jurnal Hukum Lex Generalis, 2025)
The sale and purcase agreement (PPJB) of land accompanied by a power of attorney to sell is frequently used as collateral in debt agreements. However, such a PPJB does not constitute valid legal collateral because it lacks executorial power and is susceptible to annulment by the court. This creates legal risk for creditors in the event of default by the debtor. Notaries must be held accountable for eansuring the accuracy and conformity of documents with actual conditions to prevent legal losses. Therefore, it is advi for creditors to use legally recognized forms of collateral, such a mortage risk (hak tanggungan), to ensure legal protection and debt repayment certanly. Legal protection for creditors can also be strenghened through fair contractual clauses and legal action in cases of default or unlawful condut.